2021
DOI: 10.2147/jaa.s299186
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Asthma on the Association Between Pulmonary Function and Obesity: A 16-Year Longitudinal Study

Abstract: Background Asthma and obesity are important public health issues around the world. Obesity is considered a risk factor associated with the severity and incidence of asthma. We investigated the relationships between poor pulmonary function (defined by forced vital capacity (FVC) and percentage of predicted FVC (FVC%)) and obesity. Methods This is a retrospective longitudinal study using the MJ health examination database in Taiwan from 2000 to 2015. There were 160,609 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
3
6
1
Order By: Relevance
“…Interestingly, Comparison between studied groups as regard spirometry parameters (FEV1, FVC % of predicted and FEV1/FVC) showed that there was no statistically significant difference between the groups. This is contrary to a recent study by Huang and coworkers (24) who found that adults who had both abnormal BMI (overweight and obesity) had substantially decreased pulmonary function tests in asthmatic and non-asthmatic patients. Other previous studies have reported slightly lower FEV1/FVC in adults with asthma (25) .…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, Comparison between studied groups as regard spirometry parameters (FEV1, FVC % of predicted and FEV1/FVC) showed that there was no statistically significant difference between the groups. This is contrary to a recent study by Huang and coworkers (24) who found that adults who had both abnormal BMI (overweight and obesity) had substantially decreased pulmonary function tests in asthmatic and non-asthmatic patients. Other previous studies have reported slightly lower FEV1/FVC in adults with asthma (25) .…”
Section: Discussioncontrasting
confidence: 99%
“…A population-based cohort study in The Netherlands of the epidemiology of obesity showed that, in 472 patients with asthma, obesity (BMI > 30 kg/m 2 ) was associated with lower FEV 1 and FVC than non-obesity 32 . Another longitudinal study also showed that obesity was significantly associated with decreased lung function (FVC), and the risk was higher in patients with asthma than in those without asthma 33 , which supported the present results. As for the mechanisms, decreased responses to corticosteroid therapy, which is one of the factors related to the severity of asthma with obesity 21 , 34 , might be involved.…”
Section: Discussionsupporting
confidence: 91%
“…7 Our previous retrospective longitudinal study revealed that the annual increment of body mass index (BMI) is significantly associated with accelerated lung function decline, with a greater risk of acute exacerbation in asthmatics than non-asthmatics. 8 With the advancement of whole genome sequencing in decades, genome-wide association studies (GWAS) have revealed shared genetic risk factors of obesity-related traits, indicated by body-mass index and high-density lipoprotein with asthma. 9–11 Zhu et al indicated that the impact of BMI-based obesity trait-related genes on populations with later-onset and non-atopic asthma is greater than those with early onset and atopic asthma by conducting a GWAS of 457,822 individuals in the UK Biobank.…”
Section: Introductionmentioning
confidence: 99%